ON THE METHODOLOGY OF PREPARING FUTURE AGRICULTURAL SPECIALISTS FOR PROFESSIONAL ACTIVITY IN A VIRTUAL LEARNING ENVIRONMENT - Sultanov Elimbet Kalimbetovich (Web of Journals Publishing, 2025)
In the article, in order to ensure the quality of education, it begins with the identification of the necessary results of education. A competent approach is the quality of education in the modern education system. A competent approach is a ministry of students. Educational activity is important.
Keywords: higher education, approach, competence, agriculture, cognitive, motivational, creative education, practical education.